Pengaruh Motivasi Belajar dan Inovasi Organisasi terhadap Hasil Belajar Agama Buddha Siswa SMA Denpasar - Lionie Permata Dewi; Isomudin Isomudin; Muljadi Muljadi (Institut Nalanda, 2024)
Learning outcomes are important for a child to be able to have the ability and also have knowledge.This study uses quantitative research methods. Data collection techniques in quantitative research use a questionnaire developed through the indicators of each variable. The results of hypothesis testing the effect of the functional relationship (X1) on (Y) with the regression equation = 23.349 + 0.812 X1, (2) There is an influence (X2 ) on (Y) with the regression equation = 23.749 + 0.827 X2, (3) There is an influence (X1) and (X2) together on (Y) with the regression equation = 24.159 + 1.229 X1 – 0.483 X2. The regression coefficient value of Learning Motivation (X1) is 0.812, meaning that if the Learning Motivation variable (X1) increases by 1% assuming Organizational Innovation (X2) and Constant (a) is 0 (zero) then Learning Outcomes (Y) increase by 0.812, p. it shows that the learning motivation variable (X1) contributes positively to the learning outcomes (Y) so that the students' learning motivation (X1) will increase the students' learning outcomes (Y).